Colour vision of domestic chicks - Osorio, D; Vorobyev, M; Jones, C D (Journal of experimental biology, 1999)
The colour vision of domestic chicks (Gallus gallus) was investigated by training them to small food containers decorated with tilings of grey and coloured rectangles. Chicks learn to recognise the colour quickly and accurately. Chicks have four types of single-cone photoreceptor sensitive to ultraviolet, short-, medium- or long-wavelength light. To establish how these receptors are used for colour vision, stimuli were designed to be distinguished only by specific combinations of receptors. We infer (1) that all four single cones are used, and (2) that their outputs are encoded by at least three opponency mechanisms: one comparing the outputs of ultraviolet- and short-wavelength-sensitive receptors, one comparing the outputs of medium- and long-wavelength receptors and a third comparing of the outputs of short- and long- and/or medium-wavelength receptors. Thus, the chicks have tetrachromatic colour vision. These experiments do not exclude a role for the fifth cone type, double cones, but other evidence suggests that these cones serve luminance-based tasks, such as motion detection, and not colour recognition.